Impact Analysis of Implementing School Safe Zones (Case Study: ZoSS at SMPN 15 Padang and MTsN 1 Padang) - Oktaviani, Oktaviani; Leonanda, Benny Dwika; Putri, Trigenta Sommya (Universitas Negeri Padang, 2024)
The Padang city government has implemented the ZoSS program for two schools located close to each other in Koto Tangah District, namely SMPN 15 Padang and MTsN 1 Padang located on Jalan Adinegoro, Batipuh Panjang District. However, the function of the presence of ZoSS in these two schools is considered to be ineffective because there are still many motorbike drivers who travel at speeds exceeding the permitted speed limit when crossing the ZoSS area, even though the facilities are in accordance with the Director General of Land Transportation's regulations Number: SK3582/AJ.403/DRJD/2018. Therefore, the research aims to review the impact of implementing ZoSS on the speed of motorized vehicles and the characteristics of road crossing behavior on ZoSS in this area. The data used was obtained by conducting surveys and direct observations in the field. The survey carried out included a survey of instantaneous speed data (spot speed) of vehicles when crossing the ZoSS, and a survey of the characteristics of road crossing behavior on the ZoSS. after school.The results of the research concluded that the implementation of the ZoSS program at SMPN 15 Padang and MTsN 1 Padang, located on Jalan Adinegoro, was considered ineffective in terms of motor vehicle speed, because it exceeded the maximum speed limit (30 km /hour) when crossing the ZoSS with an average speed of 46.75 km/hour with the percentage of vehicles complying with the permitted speed still below 50%, and the behavior of pedestrians when crossing in the ZoSS area is categorized as